Temperature-induced phase transition from cycloidal to collinear antiferromagnetism in multiferroic Bi0.9Sm0.1FeO3 driven by f-d induced magnetic anisotropy - Johnson, R; McClarty, P; Khalyavin, D; Manuel, P; Svedlindh, P; Knee, C (American Physical Society, 2017)
In multiferroic BiFeO3 a cycloidal antiferromagnetic structure is coupled to a large electric polarization at room temperature, giving rise to magnetoelectric functionality that may be exploited in novel multiferroic-based devices. In this paper, we demonstrate that substituting samarium for 10% of the bismuth ions increases the periodicity of the room-temperature cycloid, and upon cooling to below ∼15 K the magnetic structure tends towards a simple G-type antiferromagnet, which is fully established at 1.5 K. We show that this transition results from f-d exchange coupling, which induces a local anisotropy on the iron magnetic moments that destroys the cycloidal order - a result of general significance regarding the stability of noncollinear magnetic structures in the presence of multiple magnetic sublattices.